2018
DOI: 10.1088/1361-6528/aabbff
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites: suitable alternatives as antimicrobial agents

Abstract: The exploration of nanocomposites has gained a strong research following over the last decade. These materials have been heavily exploited in several fields, with applications ranging from biosensors to biomedicine. Among these applications, great advances have been made in the field of microbiology, specifically as antimicrobial agents. This review aims to provide a comprehensive account of various nanocomposites that elucidate promising antimicrobial activity. The composition, physical and chemical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 179 publications
(222 reference statements)
0
44
0
Order By: Relevance
“…Biocompatibility of nanocellulose makes it potential candidate for biomedical applications . Previous reports on nanocellulose‐Ag NPs composites showed that it can be utilized for various biological applications . Poly(methacrylic acid) (PMAA) protected Ag NP functionalized CNF films showed fluorescence and antimicrobial activity .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Biocompatibility of nanocellulose makes it potential candidate for biomedical applications . Previous reports on nanocellulose‐Ag NPs composites showed that it can be utilized for various biological applications . Poly(methacrylic acid) (PMAA) protected Ag NP functionalized CNF films showed fluorescence and antimicrobial activity .…”
Section: Introductionmentioning
confidence: 94%
“…Recently, Nanocellulose is explored as matrix material for the fabrication of inorganic‐organic nanocomposites as it can provide synergistic properties with environmentally benign and energy efficient production routes. Nanocellulose based composites integrated with optical, electronic, magnetic and mechanical properties of inorganic nanomaterials showed broad range of applications like catalyst, energy storage, sensors, electronics, water purification, antimicrobial properties etc.…”
Section: Introductionmentioning
confidence: 99%
“…Both graphene and AgNPs have been combined with polymer matrices to develop antimicrobial materials [30]. Polymer nanofibrous patches containing antimicrobial agents have been fabricated via electrospinning for application in various fields [31].…”
Section: Introductionmentioning
confidence: 99%
“…The atoms also have a weakly delocalized π‐electron cloud that is orientated in the z‐axis (Greshnov, 2014; Luo, Qiu, Lu, & Ni, 2013; Novoselov et al., 2007). The antibacterial properties of carbonaceous nanomaterials have been widely investigated and reported in the literature; however, their antiviral properties are unknown (Matharu, Ciric, & Edirisinghe, 2018; Matharu, Ciric, et al, 2018; Matharu et al., 2018, 2020). Studying the interaction between graphene nanomaterials and viral pathogens is of immense interest, to allow for the development of new antiviral treatments.…”
Section: Introductionmentioning
confidence: 99%